Efficacy and safety of LAS41008 (dimethyl fumarate) in adults with moderate‐to‐severe chronic plaque psoriasis: a randomized, double‐blind, Fumaderm®‐ and placebo‐controlled trial (BRIDGE). (15th November 2016) - Mrowietz, U.; Szepietowski, J.C.; Loewe, R.; van de Kerkhof, P.; Lamarca, R.; Ocker, W.G.; Tebbs, V.M.; Pau‐Charles, I.
Summary: Background: Fumaric acid esters (FAEs) are recommended in international guidelines for induction and long‐term treatment of adults with moderate‐to‐severe chronic plaque psoriasis. The fixed combination Fumaderm ® is approved in Germany, with dimethyl fumarate (DMF) being the main active ingredient. Objectives: To assess the efficacy and safety of a new formulation of DMF (LAS41008), compared with placebo and Fumaderm ®, in adults with moderate‐to‐severe chronic plaque psoriasis. Methods: In this phase III, double‐blind, placebo‐controlled, noninferiority trial (BRIDGE, NCT01726933, EudraCT 2012‐000055‐13), patients were randomized to receive LAS41008, Fumaderm ® or placebo (2 : 2 : 1) for 16 weeks, uptitrating to a maximum daily DMF dose of 720 mg, depending upon individual response. The coprimary end points were the percentage of patients achieving ≥ 75% improvement in Psoriasis Area and Severity Index (PASI 75) and the percentage achieving a score of 'clear' or 'almost clear' in the Physician's Global Assessment (PGA) at week 16. Results: In total, 671 patients were randomized and included in the full analysis set ( n = 267, LAS41008; n = 273, Fumaderm ® ; n = 131, placebo). At week 16, 37·5% of patients treated with LAS41008 achieved PASI 75, compared with 15·3% receiving placebo (superiority for LAS41008 vs. placebo: P < 0·001) and 40·3% receiving Fumaderm ® (noninferiority for LAS41008 vs. Fumaderm ® : P < 0·001). Overall, 33% of patients treated with LAS41008 were 'clear' or 'almost clear' in the PGA at week 16, compared with 13·0% receiving placebo ( P < 0·0001; LAS41008 superiority vs. placebo) and 37·4% receiving Fumaderm ® . Most treatment‐related adverse events were classed as 'mild' in severity. Conclusions: LAS41008 (DMF) is effective in the treatment of adults with moderate‐to‐severe chronic plaque psoriasis. Abstract : What's already known about this topic? A combination of fumaric acid esters (FAEs), including dimethyl fumarate (DMF), is approved for the treatment of moderate‐to‐severe psoriasis in Germany, with a positive risk–benefit profile for long‐term use. Despite being recommended in international treatment guidelines, FAEs are not available in most European countries. What does this study add? This international, randomized, double‐blind trial demonstrates the efficacy and safety of LAS41008 (DMF) for the treatment of adults with moderate‐to‐severe chronic plaque psoriasis. Linked Comment: Balak. Br J Dermatol 2017;176 :563–564 . Plain language summary available online